(3GdCQHYjf GdeJHGjfIs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s ((3GHh GdHQ jhfS Hf YHO Gddg GdbGOQi s)
(3ChdgG (B:s
(3CeG HYO agPg GQHYhf MOjKkG ef eQhjGJi GdYGdjGJ GdMOjK GdChd Cf QShd Gddg Udi Gddg Ydjg hSde bGd (B:" (3GdQGMehf jQMege GdQMef JHGQc hJYGdi CQMehG ef ai GdGQV jQMece ef ai GdSeGA (B" s
(3BNQgG (B:s
(3GdMOjK GdNGeS hGdGQHYhf bQCJ Ydi eQje HfJ CMeO Hf eMeO hbO bGd GdfHi Udi Gddg Ydjg hSde (B:" (3ef MaX Ydi GeJi GQHYjf MOjKkG fYeg Gddg jhe GdbjGeI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI cJHJ ai MjGI GdeDda hYdjgG NWg HUMI SeGYg Ydjg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs